A framework to guide the design of environments coupling mobile and situated technologies - Bedwell, Benjamin D. (2010)
An increasing number of devices are being situated in public spaces yet interactions with such devices are problematic: they tend to be impersonal and subject to social apprehension while devices suitable for specific tasks may be difficult to locate. This thesis considers how one might design for these environments to overcome these issues and deliver engaging user experiences. It proposes the coupling of the interactive features of mobile and situated devices to facilitate personalised interactions with those situated devices. The thesis explores coupling techniques that extend the computational capabilities of the situated device through the addition of the input, output and storage capabilities of the mobile device. Finally it considers how multiple points of coupling can be used to link sequences of interactions with different situated devices providing rich, cohesive experiences across an environment. The thesis presents a novel framework that builds upon previous work. Existing work is reviewed that links mobiles with single situated displays, and that uses mobiles for mediating exploration of physical spaces to address the lack of work addressing multiple situated de-vices in public. This review grounds a proposal and elaboration of a core model of interaction within a coupling environment, providing the basis for a design framework. This was sup-ported by the implementation of a test-bed that consisted of six couples in various configura-tions, underpinned by a software infrastructure. Formative user studies refined the framework and revealed novel aspects of the user experi-ence for study. It was found that through support for narrative and personal orchestration, coupling environments afford personalised trajectories. By designing for personal trajectories the visitor has a more enjoyable personal experience and seeks to improve the experiences of others. In addition, coupling environments support social experiences; the step-by-step nature of a visitor’s trajectory through the coupling environment lends itself to gradually introducing visitors to social coupled interaction and reducing social awkwardness.